2010
DOI: 10.3109/10428190903437629
|View full text |Cite
|
Sign up to set email alerts
|

Kinase domain mutations and responses to dose escalation in chronic myeloid leukemia resistant to standard dose imatinib mesylate

Abstract: We studied kinase domain (KD) mutations, response to dose escalation, event free survival (EFS), and overall survival (OS) of 90 patients with chronic phase CML who were resistant to imatinib mesylate (IM) 400 mg. IM was escalated to 800 mg daily. There were 65 patients with hematologic failure and 25 with cytogenetic failure. Median duration on IM at resistance detection was 18 months (range, 3-48). Twenty nine (32.2%) patients had KD mutations. Of the 29, the most common were T315I in nine (31.2%) and G250E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
(47 reference statements)
2
8
0
Order By: Relevance
“…CCR can be attained in 50% of patients who do not achieve CCR or lose CCR, but for those with loss of CHR or nonachievement of CHR, the chance of attaining CCR was only 18%. 16,51 One study reported that approximately 25% of patients who experienced treatment failure with imatinib can regain optimum cytogenetic responses with dose escalation. 23 …”
Section: Methodsmentioning
confidence: 99%
“…CCR can be attained in 50% of patients who do not achieve CCR or lose CCR, but for those with loss of CHR or nonachievement of CHR, the chance of attaining CCR was only 18%. 16,51 One study reported that approximately 25% of patients who experienced treatment failure with imatinib can regain optimum cytogenetic responses with dose escalation. 23 …”
Section: Methodsmentioning
confidence: 99%
“…T315I was the most commonly seen mutation in our study (31.8%), Rajappa et al . [ 20 ] (31%) which was our previous institutional study and Suresh-Babu et al . [ 27 ] (16.6%) studies.…”
Section: Discussionmentioning
confidence: 55%
“…Our study comprised 269 CML patients with imatinib treatment failure. The median age was 36 years (18-66 years) and the sex ratio was 1.7:1, whereas in other studies by Quintas Cardama Alfonso et al .,[ 17 ] Jabbour et al .,[ 18 ] Cortes et al .,[ 19 ] Rajappa et al .,[ 20 ] and Mishra et al .,[ 21 ] the median age was 52 years (18–79), 57 years (25–82), 51 years (17–96), 36 years (18–65), and 35 years, respectively. The sex ratio was 1.08:1, 1.6:1, 2.7:1, and 1.6:1 in the studies done by Quintas Cardama Alfonso et al .,[ 17 ] Jabbour et al .,[ 18 ] Rajappa et al .,[ 20 ] and Mishra et al .,[ 21 ] respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Similarly, it has been widely suggested that some patients with mutations may have an improved response following imatinib dose escalation although there is no consensus on the mutations to which this applies. [56][57][58] BCR-ABL mutations have been found to cluster into specific regions of the ABL kinase domain ( Table 2), including the phosphate-binding (P)-loop (residues 248-255), drug contact site (T315/F317), catalytic domain (residues 350-363) and A-loop (residues 381-402), although mutations are also found in other regions. 22,51,53,[59][60][61] Several analyses have found a relationship between clinical outcome on imatinib and type/location of BCR-ABL mutation.…”
Section: Clinical Significance Of Mutations For Second-line Tki Treatmentioning
confidence: 99%